HUBUNGAN RIWAYAT PEMAKAIAN KONTRASEPSI DENGAN RIWAYAT PENYAKIT KRONIS PADA WANITA USIA 45-55 TAHUN - Rahayyu, Rini; Zulliati, Zulliati; Mahdiyah, Dede (Midwifery And Complementary Care, 2024)
Background: Menopause is a normal life event which is marked by the physiological cessation of the last menstruation which is related to the elderly level of a woman. Women who use hormonal contraception will enter menopause longer or older. Objective: To determine the relationship between history of contraceptive use and history of chronic disease using the menopause rating scale (MRS) in women aged 45-55 years at the Dirgahayu Health Center, Kotabaru District. Methods: This study used an analytic survey with a cross-sectional approach. A sample of 30 mothers used accidental sampling. Data collection used a questionnaire which was analyzed in the form of a frequency distribution which was analyzed using the chi square test. Results: Most of the history of contraception use in women aged 45-55 years used hormonal as many as 19 people (63.3%). Mothers with mild and severe premenopausal complaints were 15 people (50.0%). Obtained a significant value of p = 0.014 (p.value <0.05), there is a relationship between history of contraceptive use and a history of chronic disease using the menopause rating scale (MRS) in women aged 45-55 years. Conclusion: there is a relationship between history of contraceptive use and history of chronic disease using the menopause rating scale (MRS) in women aged 45-55 years.